Kajian Psikologis terhadap Tokoh Utama Kinan dalam Novel Layangan Putus Karya Mommy ASF - Susilawati, Susilawati; Diana, Ari (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study examines the psychological dimensions of the main character, Kinan, in the novel Layangan Putus by Mommy ASF, through the lens of Freudian psychoanalysis, particularly the constructs of the id, ego, and superego. The research addresses three main questions: (1) How are the id, ego, and superego manifested in Kinan’s character? (2) What psychological problems are portrayed in Kinan’s character? (3) How are defense mechanisms employed by Kinan to cope with internal conflicts? This research adopts a qualitative approach using content analysis. The primary data source is the first edition of the novel published by RDM Publisher in 2020. Data were collected through written documentation and analyzed using descriptive qualitative methods. The findings reveal that Kinan’s character reflects a conflicted id marked by discomfort and unmet needs, an ego dominated by anger, and a superego with high personal moral standards. Five major psychological issues were identified: mood disorders (sadness, anger, disappointment), anxiety, stress, somatoform disorders, and personality disorders (including borderline, obsessive-compulsive, histrionic, narcissistic, and adventitious types). These disorders are further explored through her coping strategies and psychological defense mechanisms, illustrating the complex internal struggles she experiences. The study concludes that Kinan's psychological turmoil serves as a central force driving the narrative conflict.